Noise and disturbance caused by vehicles crossing cattle grids: Comparison of installations. (15th January 2017) - Watts, Greg; Pheasant, Rob; Khan, Amir
Abstract: Cattle grids are used on roads and tracks to prevent grazing animals from leaving an open space without fencing onto a more controlled area where access to the road from surrounded land is more limited. They are widely used in the UK at the entrances to common and moorland areas where animals are free to roam, but also on private drive entrances. Typically, they consist of a series of metal bars across the road that are spaced so that an animal's legs would fall through the gaps if it attempted to cross. Below the grid is a shallow pit that is intended to further deter livestock from using that particular crossing point. The sound produced as vehicles cross these devices is a characteristic low frequency "brrrr" where the dominant frequencies relates to the bar passage frequency under the tyres. The sound can be disturbing to riders and their horses and walkers and residents living close by as evidenced by press reports and the need to consider noise aspects in planning for new installations. For this reason and due to the lack of available information on the size and nature of the problem measurements and recordings have been made at a number of sites in Yorkshire in the UK. In addition, questionnaire surveys of residents living close by and façade measurements have also been used to gauge impact. Results show that there is a wide variation in the maximum noise level produced by cattle grids of apparently similar design. This can be related to impact noise produced by the movement of all or part of the grid as the frame comes under impulsive loading as the vehicle crosses. It was further established that some residents living close to the cattle grids were disturbed by the noise, and in some cases vibration, and wanted them removed or suitably modified.